Comparative Evaluation of Changes in Haematological Parameters in Female Albino Wistar Rats Treated with Ethanolic Extract of The Leaves and Bark of Ficus benghalensis Linn - Amali, El-Khalid Oinonyilokwu Onche; Sesugh, Benedicta Dogo; Iwuchukwu, Bruno Obinaa; Oladele, Emmanuel Tolani (Sahel Journal of Life Sciences FUDMA, 2025)
Ficus benghalensis Linn holds significant trado-medicinal properties, and it is reputed for its therapeutic potential. Various parts of this species are utilized in treating various ailments. This study was designed to evaluate the haematological effects of ethanolic extracts of the leaf and bark of F. benghalensis in female Wistar rats. Plant materials were collected from an open field, shade-dried, and ground to powder, thereafter extracted using ethanol, followed by distillation using a Soxhlet extractor, and phytochemical screening was conducted. Twenty-five (25) female rats were procured and divided into five (5) groups of five rats each: Group 1- control, groups 2, 3, 4, and 5 as a high-dose leaf; low-dose leaf; high-dose bark and low-dose bark respectively. Extracts (800mg/kg; vol: 1.2mL) and 400mg/kg; vol: 0.6mL) for high and low doses were orally administered for 28 days and the weight of rats was monitored during the period. The blood sample was collected and analyzed using an automated haematology analyzer. Results revealed the following bioactive compounds: flavonoids, tannins, phenols, saponins, alkaloids, and steroids. Percentage change in body weight (%) across the groups 1-5: included 7.08%, - 0.79%, 5.45%, 5.05%, and 0.75% respectively. The high-dose leaf extract group showed a significantly (p < 0.05) reduced rate of weight gain compared to both the control and the other treated groups. Haematological analysis revealed a non-significant (p ˃ 0.05) elevation across these groups suggesting stimulatory effects on erythropoiesis and thrombopoiesi.